2021
DOI: 10.3389/fneur.2021.735999
|View full text |Cite
|
Sign up to set email alerts
|

More Than Just Static: Dynamic Functional Connectivity Changes of the Thalamic Nuclei to Cortex in Parkinson's Disease With Freezing of Gait

Abstract: Background: The thalamus is not only a key relay node of the thalamocortical circuit but also a hub in the regulation of gait. Previous studies of resting-state functional magnetic resonance imaging (fMRI) have shown static functional connectivity (FC) between the thalamus and the cortex are disrupted in Parkinson's disease (PD) patients with freezing of gait (FOG). However, temporal dynamic FC between the thalamus and the cortex has not yet been characterized in these patients.Methods: Fifty PD patients, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 54 publications
2
11
0
Order By: Relevance
“…Moreover, the previous studies found reduced PAS scores of the thalamus and IFG was found in schizophrenia patients and ultra‐high risk for psychosis (F. Zhu et al, 2019 ). However, we found opposite pattern between the whole‐brain and intrahemispheric dFCD variances and sFCD in drug‐naïve FES patients with AVHs or NAVH, which is consistent with the findings in the previous study exploring the neural substrates of other neurological diseases, such as bipolar depression and major depressive disorders (Pang et al, 2020 ), generalized anxiety disorder (Lu et al, 2020 ), and Parkinson's disease (S. Wang, Cai, et al, 2021 ). Higher dFCD may reflect the indicative of flexible communication, but it may also be a sign of unstable interactions (S. Wang, Cai, et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Moreover, the previous studies found reduced PAS scores of the thalamus and IFG was found in schizophrenia patients and ultra‐high risk for psychosis (F. Zhu et al, 2019 ). However, we found opposite pattern between the whole‐brain and intrahemispheric dFCD variances and sFCD in drug‐naïve FES patients with AVHs or NAVH, which is consistent with the findings in the previous study exploring the neural substrates of other neurological diseases, such as bipolar depression and major depressive disorders (Pang et al, 2020 ), generalized anxiety disorder (Lu et al, 2020 ), and Parkinson's disease (S. Wang, Cai, et al, 2021 ). Higher dFCD may reflect the indicative of flexible communication, but it may also be a sign of unstable interactions (S. Wang, Cai, et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…However, we found opposite pattern between the whole‐brain and intrahemispheric dFCD variances and sFCD in drug‐naïve FES patients with AVHs or NAVH, which is consistent with the findings in the previous study exploring the neural substrates of other neurological diseases, such as bipolar depression and major depressive disorders (Pang et al, 2020), generalized anxiety disorder (Lu et al, 2020), and Parkinson's disease (S. Wang, Cai, et al, 2021). Higher dFCD may reflect the indicative of flexible communication, but it may also be a sign of unstable interactions (S. Wang, Cai, et al, 2021). And weaker sFCD may be the result of unstable interactions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, several studies suggested that brain connectivity among various brain regions changed in PD patients, which might be related to the pathological changes of various brain regions occurring in PD patients. It was reported that functional connectivity was decreased in the thalamic nuclei and associative cortical areas related to the sensorimotor integration or cognitive function in PD patients with freezing of the gate, and the changes in connectivity was associated with disease severity (Wang et al, 2021 ). In addition, it was also reported that the treatment for PD patients could modify the changed brain connectivity: the subthalamic nucleus-deep brain stimulation showed increased functional connectivity of the supplementary motor cortex, putamen, inferior frontal gyrus, and dorsal frontoparietal network, which was also correlated with changes of UPDRS-III scores (Huang L. C. et al, 2022 ), indicative of the importance of functional connectivity in the treatment of PD.…”
Section: Discussionmentioning
confidence: 99%
“… Structural DTI Functional Connectivity (FC) ROI seed-based analyses Cross-sectional Diffuse WM deficits in tracts projecting from PPN to motor, sensory & cognitive areas (C/T HC). Lower FC of right PPN with right MTG, ITG, & bilateral CRB (C/T to HC & FoG-) Interference AND/OR Perceptual Dysfunction Wang et al (2021) 25 FoG+ 25 FoG- 25 HC OFF H&Y, LEDD, MMSE, UPDRS-III, new FoG-Q and clockwise vs anti-clockwise turning. Functional connectivity (FC) ROI seed-based analyses Cross-sectional Correlational (indirect with FoG-Q scores) Higher dynamic FC between left thalamic nuclei and right IPL (positively correlated with N -FoGQ) & left PCG (C/T FoG- & HC).…”
Section: Structural and Resting-state Functional Connectivity Studies...mentioning
confidence: 99%